National Law Development Perspective on Job Creation Law: A Critique - Rilo Pambudi. S (Arena Hukum, 2024)
Choosing ‘shortcuts’ is not always the best approach, especially when establishing national legal policy. For example, the establishment of Law No. 6 of 2023 on job creation (Job Creation Law) was intended to replace and eliminate the conditionally unconstitutional status of Law No. 11 of 2020 on job creation (Law No. 11 of 2020). The issue arises because the Job Creation Law was established through the issuance of government regulations instead of laws. This approach is more expedient than standard legislative amendments, but it reflects the government’s arrogance in the development of Indonesia’s law. Therefore, this article aims to analyse the establishment of the Job Creation Law, examine its justification based on a purported compelling exigency and explore its implications for national legal development in light of Constitutional Court Decision No. 91/PUU-XVIII/2020. Through a socio-legal inquiry, this study demonstrates that establishing Job Creation Law through a Perppu fails to meet the requirement of compelling exigency and undermines meaningful participation in improving Law No. 11 of 2020, as mandated by the Constitutional Court. The findings further suggest that the enactment of the Job Creation Law reflects an authoritarian approach to national law development, with its substance leaning towards orthodox law development.